Isolation and Expression in Escherichia coli of cslA and cslB, Genes Coding for the Chondroitin Sulfate-Degrading Enzymes Chondroitinase AC and Chondroitinase B, Respectively, from Flavobacterium heparinum - Tkalec, Ana Lydia (American Society for Microbiology, 2000)
In medium supplemented with chondroitin sulfate, Flavobacterium heparinum synthesizes and exports two chondroitinases, chondroitinase AC (chondroitin AC lyase; EC 4.2.2.5) and chondroitinase B (chondroitin B lyase; no EC number), into its periplasmic space. Chondroitinase AC preferentially depolymerizes chondroitin sulfates A and C, whereas chondroitinase B degrades only dermatan sulfate (chondroitin sulfate B). The genes coding for both enzymes were isolated from F. heparinum and designated cslA (chondroitinase AC) and cslB (chondroitinase B). They were found to be separated by 5.5 kb on the chromosome of F. heparinum, transcribed in the same orientation, but not linked to any of the heparinase genes. In addition, the synthesis of both enzymes appeared to be coregulated. The cslA and cslB DNA sequences revealed open reading frames of 2,103 and 1,521 bp coding for peptides of 700 and 506 amino acid residues, respectively. Chondroitinase AC has a signal sequence of 22 residues, while chondroitinase B is composed of 25 residues. The mature forms of chondroitinases AC and B are comprised of 678 and 481 amino acid residues and have calculated molecular masses of 77,169 and 53,563 Da, respectively. Truncated cslA and cslB genes have been used to produce active, mature chondroitinases in the cytoplasm of Escherichia coli. Partially purified recombinant chondroitinases AC and B exhibit specific activities similar to those of chondroitinases AC and B from F. heparinum.